Nrf2, but not β‐catenin, mutation represents an early event in rat hepatocarcinogenesis. Issue 3 (22nd April 2015) - Zavattari, Patrizia; Perra, Andrea; Menegon, Silvia; Kowalik, Marta Anna; Petrelli, Annalisa; Angioni, Maria Maddalena; Follenzi, Antonia; Quagliata, Luca; Ledda‐Columbano, Giovanna Maria; Terracciano, Luigi; Giordano, Silvia; Columbano, Amedeo
<x xml:space="preserve">Abstract</x> Hepatocellular carcinoma (HCC) develops through a multistage process, but the nature of the molecular changes associated with the different steps, the very early ones in particular, is largely unknown. Recently, dysregulation of the NRF2/KEAP1 pathway and mutations of these genes have been observed in experimental and human tumors, suggesting their possible role in cancer development. To assess whether Nrf2/Keap1 mutations are early or late events in HCC development, we investigated their frequency in the rat Resistant Hepatocyte model, consisting of the administration of diethylnitrosamine followed by a brief exposure to 2‐acetylaminofluorene. This model enables the dissection of all stages of hepatocarcinogenesis. We found that Nrf2/Keap1 mutations were present in 71% of early preneoplastic lesions and in 78.6% and 59.3% of early and advanced HCCs, respectively. Mutations of Nrf2 were more frequent, missense, and located in the Nrf2‐Keap1 binding region. Mutations of Keap1 occurred at a much lower frequency in both preneoplastic lesions and HCCs and were mutually exclusive with those of Nrf2. Functional in vitro and in vivo studies showed that Nrf2 silencing inhibited the ability of tumorigenic rat cells to grow in soft agar and to form tumors. Unlike Nrf2 mutations, those of Ctnnb1, which are frequent in human HCC, were a later event as they appeared only in fully advanced HCCs (18.5%). Conclusion: In the Resistant Hepatocyte model of hepatocarcinogenesis the onset of Nrf2 mutations is a very early event, likely essential for the clonal expansion of preneoplastic hepatocytes to HCC, while Ctnnb1 mutations occur only at very late stages. Moreover, functional experiments demonstrate that Nrf2 is an oncogene critical for HCC progression and development. (Hepatology 2015;62:851‐862)